2016
DOI: 10.1111/cdev.12518
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations Between the Quality of Mother–Infant Interactions and Brain Development Across Infancy

Abstract: The aim of this study was to investigate if normative variations in parenting relate to brain development among typically-developing children. A sample of 352 mother-infant dyads came to the lab when infants were 5, 10, and 24 months of age (final N = 215). At each visit, child resting EEG was recorded. Mother-infant interactions were videotaped at the 5-month visit. The results indicated that higher-quality maternal behavior during mother-infant interactions predicted higher frontal resting EEG power at 10 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 131 publications
(120 citation statements)
references
References 119 publications
7
112
0
1
Order By: Relevance
“…We examine whether maternal positive affect and intrusive behavior measured at 5 months in the context of two play based interactions predicts infants’ attention behavior and associated neural activity at 5 and 10 months. In a recent paper using data from the same sample of infants as the current work, we found that normative variation in caregiver behavior related to developmental change in baseline EEG power from 5 to 24 months (Bernier et al, in press). Thus, we hypothesize that early maternal caregiving behavior exhibited during regular interaction with the infant may have an effect on the development of infants’ attention behavior through its influence on the infant’s developing neurophysiological systems supporting attention development.…”
Section: The Current Studymentioning
confidence: 54%
See 2 more Smart Citations
“…We examine whether maternal positive affect and intrusive behavior measured at 5 months in the context of two play based interactions predicts infants’ attention behavior and associated neural activity at 5 and 10 months. In a recent paper using data from the same sample of infants as the current work, we found that normative variation in caregiver behavior related to developmental change in baseline EEG power from 5 to 24 months (Bernier et al, in press). Thus, we hypothesize that early maternal caregiving behavior exhibited during regular interaction with the infant may have an effect on the development of infants’ attention behavior through its influence on the infant’s developing neurophysiological systems supporting attention development.…”
Section: The Current Studymentioning
confidence: 54%
“…During this process, environmental experiences are thought to directly influence the synaptic connections that persist and are strengthened, or which are selectively eliminated due to lack of use (Greenough & Black, 1992; Nelson & Bloom, 1997; Singer, 1995). Recent work by our research group (Bernier, Calkins, & Bell, in press) has provided previously lacking empirical support for the notion that normative variation in caregiving behavior early in development is predictive of individual differences in brain development. Specifically, we found that more maternal positivity during interactions when infants were 5 months of age was associated with greater infant EEG alpha and theta baseline power at 10 and 24 months, and greater increases in baseline power between each age.…”
Section: Influence Of Caregiving On Neurophysiological Attention Procmentioning
confidence: 99%
See 1 more Smart Citation
“…However, extrinsic influences, most notably the caregiving environment, on the development of attention (Swingler, Perry, & Calkins, 2015) and cognition (Cuevas, Deater-Deckard, Kim-Spoon, Watson, Morasch, & Bell, 2014) have been noted. Although studies are beginning to expand on this basic model to include extrinsic influences on early neural maturation, attention, and cognition (Bernier, Calkins, & Bell, in press), many more are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, las madres negligentes se caracterizan por dar menos instrucciones a sus hijos/as, tener un menor nivel de actividad y estimular menos a sus hijos durante la interacción (Bousha & Twentyman,1984;Crittenden, 1981). Por tanto, estas prácticas, como elemento fundamental de los contextos de interacción, pueden incidir en la calidad del mismo, y como consecuencia en el desarrollo de los niños (Bernier, Calkins, & Bell, 2016;Orozco-Hormaza, Sánchez-Ríos, & Cerchiaro-Ceballos, 2012).…”
Section: Introductionunclassified